Recognition of the genus Habrocampulum Gauld, 1976 (Hymenoptera: Ichneumonidae: Anomaloninae) from Japan, with a new combination and a key to the species - Shimizu, So (Zootaxa, 2016)
Recognition of the genus Habrocampulum Gauld, 1976 (Hymenoptera:Ichneumonidae: Anomaloninae) from Japan, with a new combination and a key to the species